2019
DOI: 10.2478/s11686-018-00019-3
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of the Acanthocephalan Genus Filisoma (Cavisomidae) from Perciform Fishes in Rio de Janeiro, Brasil

Abstract: Background Twelve species of Filisoma Van Cleave, 1928 are recognized parasitizing tropical and subtropical fish. Four of these species were described from kyphosid fish and it has been suggested that a co-speciation may have occurred among species of Kyphosus Lacepède, 1801 and Filisoma, which could provide valuable information about the evolution history of this host-parasite system. Purpose During a survey of the helminth fauna of Kyphosus sectatrix (Linnaeus, 1758) and Kyphosus incisor (Cuvier, 1831) (Kyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…In the present mitogenomic phylogeny, P. bufonis clustered together with Cavisoma magnum , suggesting an affinity between Pseudoacanthocephalidae and Cavisomatidae. Our results agreed well with some recent phylogenetic studies based on nuclear gene sequences [ 16 , 75 ]. These indicated that the current classification of Echinorhynchida is based on unique combinations of characteristics, not shared derived features [ 13 ].…”
Section: Resultssupporting
confidence: 93%
“…In the present mitogenomic phylogeny, P. bufonis clustered together with Cavisoma magnum , suggesting an affinity between Pseudoacanthocephalidae and Cavisomatidae. Our results agreed well with some recent phylogenetic studies based on nuclear gene sequences [ 16 , 75 ]. These indicated that the current classification of Echinorhynchida is based on unique combinations of characteristics, not shared derived features [ 13 ].…”
Section: Resultssupporting
confidence: 93%
“…A number of recent studies have provided sequences of the internal transcribed spacers (ITS) (e.g. Li et al, 2017Li et al, , 2018Fernandes et al, 2019;García-Varela & Pinacho-Pinacho, 2020) and such data may provide a viable barcoding alternative to cox1 for acanthocephalans for which amplification is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite an increasing number of species descriptions in various clades of acanthocephalans, in most cases, intermediate hosts are often unknown or only inferred from knowledge of closely related parasite species (e.g. [9,37,68,157]), especially for marine acanthocephalans [27]. Elucidating life cycles is difficult because larval and juvenile stages of acanthocephalans (acanthella, cystacanth) are hardly detectable and/or difficult to identify using morphology, and because of low prevalence of infection in intermediate hosts.…”
Section: Life Cycle Of Acanthocephalans: Fragmentary Knowledgementioning
confidence: 99%